43. EXPERIENCE IN MANAGING HYPOTENSION DURING SPINAL ANESTHESIA, C-SECTION, NHI AN HOSPITAL (Vietnam Journal of Community Medicine, 2025)
Introduction: Hypotension during spinal anesthesia (SA) is a very common complication, occurring in 70-80% of women undergoing cesarean section. If not effectively prevented and managed, hypotension can lead to adverse maternal and fetal outcomes.Primary Mechanism of Hypotension: The main cause of hypotension is sympathetic blockade, which leads to vasodilation of both arteries and veins. However, the compensatory mechanisms for vasodilation and hypotension are diminished in pregnant women. Additionally, aortocaval compression due to fetal weight significantly reduces venous return to the heart, further exacerbating the severity of hypotension.Prevention and Management: Several strategies have been studied for the prevention and management of spinal anesthesia-induced hypotension, including fluid administration and physical methods. However, vasopressor use is considered the most crucial approach. Historically, ephedrine, a drug with both direct and indirect α1 and β adrenergic stimulation, was the first-line choice due to its ability to cross the placenta. However, recent studies and recommendations from many authors and obstetric anesthesia centers advocate for phenylephrine as the preferred agent. Phenylephrine selectively stimulates α1 receptors, does not cross the placenta, causes less maternal tachycardia, and is associated with a lower incidence of fetal acidosis.Research on phenylephrine for the prevention and management of hypotension during spinal anesthesia for cesarean section continues to be actively conducted in Vietnam and worldwide.Conclusion: Without prophylactic measures, hypotension during spinal anesthesia for cesarean section is almost unavoidable and poses significant risks to both mother and fetus. The main preventive strategies include vasopressor administration combined with fluid therapy. In recent years, phenylephrine has gained preference and is now considered the first-line drug for managing spinal anesthesia-induced hypotension.
Keywords: Management of hypotension; Phenylephrine; Spinal anesthesia for cesarean section